2012
DOI: 10.1002/pros.22595
|View full text |Cite
|
Sign up to set email alerts
|

Positive correlation between PEDF expression levels and macrophage density in the human prostate

Abstract: BACKGROUND In this study, we investigated the capacity of PEDF to modulate the recruitment and the differentiation of monocytes/macrophages both in vitro and in human prostate. METHODS Using Boyden chambers, we assessed PEDF effect on the migration of monocytes and chemically-activated RAW264.7 macrophages. Normal, prostatitis and prostate cancer specimens were retrospectively selected and examined by immunohistochemistry for PEDF expression and infiltration of immune CD68+macrophagic cells. PEDF expression … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 51 publications
1
19
0
Order By: Relevance
“…We have previously demonstrated that PEDF induces the migration of macrophages and their polarization towards the classically activated pathway [34]. In human prostate, we showed that PEDF expression correlates with macrophage density.…”
Section: Introductionmentioning
confidence: 68%
“…We have previously demonstrated that PEDF induces the migration of macrophages and their polarization towards the classically activated pathway [34]. In human prostate, we showed that PEDF expression correlates with macrophage density.…”
Section: Introductionmentioning
confidence: 68%
“…M1-type macrophages generally express iNOS, which is tumor-cytotoxic. Tumor progression stimulates a phenotypic switch to M2 macrophages that express arginase 1, and accelerate tumor growth, survival and metastasis (31). Similarly, it has been previously demonstrated that the density of iNOS-positive macrophages, which infiltrate the stroma, is decreased in highly aggressive gliomas compared with less aggressive cancer, which indicates that as malignant potential of the cancer increased, the cytotoxic activity of macrophages is reduced (32).…”
Section: Discussionmentioning
confidence: 93%
“…Besides inhibiting tumor angiogenesis, exogenous or naturally secreted PEDF also induces the differentiation of cancer cells to a less-malignant phenotype, 26,27 which provided the first suggestion that PEDF could reduce malignant phenotype and act directly on tumors. Moreover, PEDF reduction in prostate cancer has been linked to poor prognosis, 28,29 while increased PEDF may act directly on prostate tumors to promote apoptosis, inhibit proliferation, and strongly suppress metastasis. 16 Our data suggest that the altered expression of PEDF induced by metformin might be involved in its antitumor activity.…”
Section: Discussionmentioning
confidence: 99%